Cause lawyering when it really matters: how Istanbul lawyers reacted to events in Gezi - Elveris, Idil (Routledge Journals, Taylor & Francis Ltd, 2016)
This paper is about voluntary legal representation of detainees during the Gezi events in Istanbul in June 2013. By way of in-depth interviews conducted with attorneys who did the work, the paper seeks to understand the reasons for its emergence since there was government-funded legal aid in these matters. Another goal was to understand whether there were any ethical problems during its provision. Attorneys' primary reason to volunteer seems to be that legal aid was not working. The second reason was their identification with the protesters. They therefore engaged in defensive cause lawyering and employed the law in creative and strategic ways to fight against a government crackdown. Cause lawyering was facilitated by an autonomous legal profession, legal aid, as well as a relatively independent prosecutorial service.